1977
DOI: 10.1111/j.1365-2125.1977.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorimetric assay of cephradine, cephalexin and cephaloglycin.

Abstract: 1 A simple, rapid and reproducible fluorimetric assay for cephradine, cephalexin and cephaloglycin is described. 2 The method involves addition of formaldehyde which catalyses the formation of fluorescent derivatives. 3 The structural similarities between the side chains of these antibiotics and their identical excitation and emission spectra suggest that they may be forming similar fluorescent derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Both ampicillin (for penicillinase activity) and cephalexin (for cephalosporinase activity) were used at a concentration of 10 mM, while nitrocefin was used at a concentration of 50 ,ug/ ml as described in Materials and Methods. product was formed (1, 2), and this provided the basis for a sensitive fluorimetric assay for the total concentration of ampicilli-n or cephalexin in human plasma (1,2). However, it is impossible to adopt these procedures for detection of microbial P-lactamases, since the open ,B-lactam ring end product resulting from P-lactamase hydrolysis cannot be distinguished from the unhydrolyzed substrate after alkaline hydrolysis of the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ampicillin (for penicillinase activity) and cephalexin (for cephalosporinase activity) were used at a concentration of 10 mM, while nitrocefin was used at a concentration of 50 ,ug/ ml as described in Materials and Methods. product was formed (1, 2), and this provided the basis for a sensitive fluorimetric assay for the total concentration of ampicilli-n or cephalexin in human plasma (1,2). However, it is impossible to adopt these procedures for detection of microbial P-lactamases, since the open ,B-lactam ring end product resulting from P-lactamase hydrolysis cannot be distinguished from the unhydrolyzed substrate after alkaline hydrolysis of the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…In early studies, products of alkaline hydrolysis of ampicillin and cephalexin were found to be highly fluorescent at pH 4.2 and 5.0, respectively, in the presence of formaldehyde after heating at 100°C for 30 min, and this was the basis of fluorimetric assays for those two 3-lactam antibiotics (1,2).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] The combination of CEFA and KANA shows greater therapeutic efficacy than either drug alone in treating clinical mastitis in lactating dairy cows, caused by Staphylococcus aureus, Streptococcus dysgalactiae, Streptococcus uberis, and Escherichia coli. Moreover, literature reports various methods for the estimation of CEFA and KANA in pharmaceutical formulations either alone or in combination with other drugs by HPLC and spectroscopic methods, [6][7][8][9][10][11][12][13][14][15][16][17][18][19] but the literature is silent on the development of analytical method for simultaneous determination of CEFA and KANA in their binary mixtures.…”
Section: Introductionmentioning
confidence: 99%